POTENSI DASAR MANUSIA MENURUT IBNU TAIMIYAH DAN IMPLIKASINYA DALAM PENDIDIKAN ISLAM - Nandang Kosim; Lukman Syah (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2016)
Basic human potential which is commonly referred to in the Qur'an nature scattered in 19 letters and 19 paragraphs. Forms of the word is the word fatara 18 times, said fatiru 6 times, said yatafattarna 2 times, and said infatarat, futur, munfatir, and the nature of each 1 times. Basic human potential in the view of Ibn Taymiyyah is the innate potential that exists within the human inborn. The basic potential to lead to good or things that are positive on the basis of instinct and tendency of monotheism, that instinct compliance and serve God without any polytheism. However, in the actualization and realization in real life tended to deviate from the purpose of human creation. The social environment, as represented by parents, which cause children to be Jews, Christians, and Zoroastrians. In addition, including the potential 'Aql, Ghadhab potential and the potential that lust in man. Implications their basic human potential according to the thinking of Ibn Taymiyyah, it could be easily directed at establishing Islamic educational philosophy that is more humanistic-teosentric which follow the flow of convergence. So the individual's personality is the result of a convergence between nature as the laws, namely nature, with the influence of the surrounding nature (the environment).